2016
DOI: 10.1021/acs.iecr.6b01069
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Induced Graft Polymerization of Cationic and Fluorocarbon Monomers into Cotton: Enhanced Dyeability and Photostability

Abstract: The objective of this work was to increase color yield of direct dyes on cotton with the aid of grafted quaternary ammonium monomers. Plasma-induced graft polymerization of diallyldimethylammonium chloride (DADMAC) and [2-(acryloyloxy) ethyl] trimethylammonium chloride (AOETMAC) on cotton followed by dyeing with direct dyes was studied using different concentrations of the monomers and plasma conditions, and the color yield was evaluated using K/S measurements. Colorfastness and staining after laundering were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…To achieve the aim, a potential strategy is to enhance the affinity of reactive dyes toward the cotton fabrics. , Previous studies indicated that a few methods such as the use of cationic reactive dyes, , the development of the dyeing process, , and the modification of cotton fabrics were applicable and effective. , Among these efforts, the chemical modification of cotton fabrics was one of the most promising methods to reduce the consumption of inorganic salts in the reactive dyeing process . It was achieved by introducing amino or cationic groups into/onto cotton fibers through covalent bonding .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the aim, a potential strategy is to enhance the affinity of reactive dyes toward the cotton fabrics. , Previous studies indicated that a few methods such as the use of cationic reactive dyes, , the development of the dyeing process, , and the modification of cotton fabrics were applicable and effective. , Among these efforts, the chemical modification of cotton fabrics was one of the most promising methods to reduce the consumption of inorganic salts in the reactive dyeing process . It was achieved by introducing amino or cationic groups into/onto cotton fibers through covalent bonding .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Among these efforts, the chemical modification of cotton fabrics was one of the most promising methods to reduce the consumption of inorganic salts in the reactive dyeing process. 18 It was achieved by introducing amino or cationic groups into/onto cotton fibers through covalent bonding. 19 It was found that the amino groups are more reactive than the primary hydroxyl groups to react with the reactive dyes.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the water-soluble groups in the active dye molecular structure, anions are formed in the dyeing liquid. During the dyeing process, electrostatic repulsion occurs between the dye anions and the cellulose anions, resulting in a low dye uptake rate [1]. The addition of electrolyte salt can reduce the charge repulsion by reducing the Zeta potential and promote the absorption of dye by cotton fibers [2].…”
Section: Introductionmentioning
confidence: 99%
“…The cationization modification of cotton fiber is an effective way to achieve salt-free dyeing with reactive dyes [1,[3][4][5]. After cationic modification of cellulose fiber, the surface of the fabric possesses positive charges, which can enhance the adsorption of anionic reactive dyes and help achieve salt-free dyeing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure plasma and low pressure plasma are well known techniques for enhancing dyeability PP. A plasma discharge exposure of PP fabric followed by grafting monomers results in excellent dyeing properties [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%